Applying behavioral studies to the ecotoxicology of corals: A case study on Acropora millepora - Roepke, Lisa K.; Brefeld, David; Soltmann, Ulrich; Randall, Carly J.; Negri, Andrew P.; Kunzmann, Andreas (Frontiers in Marine Science, 2022)
Behavioral responses are considered sensitive and effective indicators of organism stress. As the demand for standardized coral toxicity tests grows, innovative tools that allow for automatic and quantitative measurements of these behaviors may complement ecotoxicological studies. The rapid growth of competitive marine algae in aquaculture systems is a major issue for generating coral spat for reef restoration, and the application of non-toxic antifouling (AF) coatings might effectively mitigate this issue. While these coatings do not appear to be toxic to sensitive coral larvae, their potential to affect larval mobility has not been tested. In this context, we tested the effect of three recently-developed and potentially non-toxic AF coatings: (i) antiadhesive, (ii) cerium dioxide (CeO2-x) nanoparticle, and (iii) encapsulated biocide dichlorooctylisothiazolinone (DCOIT) on the swimming velocity and activity of Acropora millepora coral larvae for potential use in reef-restoration activities. The behavior of 32 coral larvae per AF treatment were recorded, each for 25 min, in a self-constructed dark box with two camera recording sets in parallel. The tracking analysis was performed with the software Noldus EthoVision XT. The mean larval swimming velocity on control tiles of 93.1 ± 5.6 mm min-1 (and activity of 62.8 ± 5.2%) was nearly 2-fold faster (higher) than on the antiadhesive, (CeO2-x) nanoparticle and DCOIT coatings, respectively. Larvae exposed to the DCOIT-coated tiles remained almost stationary. Although the underlying cause and consequence of these results require further investigation, tracking of coral larval swimming behavior was identified as a reliable and feasible method for assessing potential non-lethal responses to AF coatings. As changes in behavior could have significant consequences for larval survival and settlement, they are important endpoints to consider, and the quantification of behavioral responses may be a meaningful and sensitive tool. Therefore, we recommend the use of behavioral studies for coral larval assessments in ecotoxicology as a valuable endpoint. For methodological standardization and implementation, our study also features a detailed guide for video-processing and track analysis of A. millepora coral larvae in EthoVision.